Surgical Outcomes and Clinicopathological Characteristics of Patients Who Underwent Potentially Noncurative Endoscopic Resection for Gastric Cancer: A Report of a Single-Center Experience - Hiroaki Ito; Haruhiro Inoue; Haruo Ikeda; Noriko Odaka; Akira Yoshida; Hitoshi Satodate; Manabu Onimaru; Daisuke Takayanagi; Esperanza Grace Santi; Shin-ei Kudo (Gastroenterology Research and Practice)
Background. Standard treatment of early gastric cancer (EGC) after endoscopic resection with risk factors of nodal metastases and incomplete resection is controversial. We investigated optimal management for the patients with potentially noncurative EGC after endoscopic resection. Methods. We retrospectively examined clinicopathological data and surgical outcomes of all patients with clinically solitary gastric adenocarcinoma who underwent curative surgery after a single peroral endoscopic resection at the Digestive Disease Center of Showa University Northern Yokohama Hospital between April 2001 and December 2012. Fisher's exact test was used for univariate analysis. For multivariate analysis, stepwise multiple linear regression was used to identify independent predictors related to lymph node metastasis and remnant of primary tumor. Results. A total of 41 patients were studied. Four patients (9.8%) had lymph node metastases. Primary tumors remained in 6 patients (14.6%). Only venous invasion was statistically significant to lymph node metastasis (P=0.017). With respect to remnant of the primary tumor, pT1b2 tumor invasion (P=0.015) and horizontal margin (P=0.013) were statistically significant. Conclusions. Surgery with limited lymphadenectomy is recommended for tumors with venous invasion or pT1b2 tumor invasion, and additional endoscopic resection may be allowed for tumors with horizontal involvement.